1993
DOI: 10.1103/physrevc.47.47
|View full text |Cite
|
Sign up to set email alerts
|

Internal bremsstrahlung: Exact relativistic independent-particle-approximation calculations

Abstract: We have reformulated the relativistic theory of internal bremsstrahlung in electron capture (IBEC) and developed a numerical code for calculating a transition amplitude for any initial atomic state. All relativistic as well as screening effects are included within the independent-particle approximation. We have shown the advantage of the theory even in the pole-dominance region of the IBEC spectra, thus making it suitable for comparison with the observed spectra in experiments that search for light-and/or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In our previous work [4] we indicated that the Suric et al calculation [3] reproduces the shape and relative intensity of the partial IB spectra for ' I to within a few percent. The above normalization factor indicates that the Suric calculation essentially reproduces (to within 15%) the absolute intensity of the IB spectrum, as well.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…In our previous work [4] we indicated that the Suric et al calculation [3] reproduces the shape and relative intensity of the partial IB spectra for ' I to within a few percent. The above normalization factor indicates that the Suric calculation essentially reproduces (to within 15%) the absolute intensity of the IB spectrum, as well.…”
mentioning
confidence: 75%
“…Several half-lives have now elapsed since the completion of the IB measurement and the source strength has become sufficiently low to allow an absolute calibration. We present in this Brief Report the absolutely calibrated IB spectrum and compare the intensity to the theoretical calculation of Suric et al [3].…”
mentioning
confidence: 89%
See 3 more Smart Citations